Opioid receptors (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database - Borsodi, Anna; Bruchas, Michael; Caló, Girolamo; Chavkin, Charles; Christie, MacDonald J.; Civelli, Olivier; Connor, Mark; Cox, Brian M.; Devi, Lakshmi A.; Evans, Christopher; Höllt, Volker; Henderson, Graeme; et al. (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Opioid and opioid-like receptors are activated by a variety of endogenous peptides including [Met]enkephalin (met), [Leu]enkephalin (leu), β-endorphin (β-end), α-neodynorphin, dynorphin A (dynA), dynorphin B (dynB), big dynorphin (Big dyn), nociceptin/orphanin FQ (N/OFQ); endomorphin-1 and endomorphin-2 are also potential endogenous peptides. The Greek letter nomenclature for the opioid receptors, μ, δ and κ, is well established, and NC-IUPHAR considers this nomenclature appropriate, along with the symbols spelled out (mu, delta, and kappa), and the acronyms, MOP, DOP, and KOP. [116, 96, 88]. The human N/OFQ receptor, NOP, is considered 'opioid-related' rather than opioid because, while it exhibits a high degree of structural homology with the conventional opioid receptors [282], it displays a distinct pharmacology. Currently there are numerous clinically used drugs, such as morphine and many other opioid analgesics, as well as antagonists such as naloxone, however only for the μ receptor.